Sicherheit, Geschlecht und Minderheitenpolitik: Kritische Perspektiven auf die britische Antiterrorstrategie - Peeck-Ho, Catharina (transcript, 2017)
What are the consequences of involving the civil society in the battle against terrorism? The book examines the part Muslim women play in the British anti-terror strategy.